A Study of Efficacy of Information Systems and Performance Accountability in Governmental Agency - Ritchi, Hamzah; Irawan, Andi; Adrianto, Zaldy; Aprilianisa, Wina (The Indonesian Journal of Accounting Research, 2023)
This study aims at determining the efficacy of adopting the information system (IS) on performance accountability in the Indonesian government based on DeLone McLean's success model. Based on performance accountability reports being lodged by 77 ministries and institutions, 41 units responded. One hundred sixty-four respondents completed the questionnaire using purposive sampling, filling up two proportionate categories of independent and dependent variables. Path analysis was employed for the data analysis. The results confirm that quality elements as the exogenous factor, individually and together, significantly affect governmental performance accountability, satisfying the respected hypotheses. IS quality also shows a significant effect on information quality.